SECURITY DIMENSION OF THE GLOBAL ISSUES - Ruslan M. Kliuchnyk (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The article deals with current global issues of our time in their security dimension. An attempt has been made to outline the various directions of influence of global problems on the security architecture in today’s conditions. It was proposed to divide the global problems of our time into natural-ecological and socio-economic ones. At the same time, in our opinion, pandemics occupy an intermediate position between natural and anthropogenic problems. It has been argued that the modern economy is less vulnerable to natural disasters than it has been before, but natural disasters take more lives due to the high population density in the modern world. Human impact on the environment has been extremely destructive. Air pollution on a catastrophic scale is observed in large cities of the developing countries. Deforestation and desertification are making more and more areas uninhabitable. Global warming and climate change are seen not only in the rise in temperature, but also in the appearance of weather anomalies, the melting of glaciers, and the rise in the level of the World Ocean. The appearance of «climate migrants» has been explained to be one of the consequences of climate change. The combination of natural and social dimensions of global issues has been illustrated with the examples of conflicts over water. Socio-economic problems are mostly determined by the imperfection of society. This article has dealt with the demographic problem in different dimensions: in the Western countries there is a demographic crisis, and in the developing countries there is a demographic explosion, which has been shown using the example of Nigeria, Egypt, Bangladesh, Ethiopia, etc. Poverty in these countries has an important impact on economic security. A large number of people do not have the basic necessities for life (food, safe water and sanitation, shelter, healthcare, etc.) and live in conditions of absolute poverty. In some countries, the literacy rate is still quite low. The globalisation of criminal activity also a danger. Some countries, such as Haiti, can fall under the control of criminal groups. Terrorism is a type of crime that deserves to be investigated separately for many reasons. All the listed problems are extremely urgent in the conditions of inefficient political management. Solving issues related to security and overcoming the consequences of global issues is possible only in the presence of an effectively functioning public administration system. But creating a good governance system is a difficult task under conditions of dictatorship or the absence of legitimate state power. The issue of supporting international security in all spheres is a topical problem in international politics. It has been underlined that joint efforts can help to overcome of the explored issues.